Efeito de tratamentos térmicos na resistência flexural de uma vitrocerâmica reforçada por leucita - Aurélio, Iana Lamadrid (2014)
The aim of this study was to investigate the effect of heat treatments on the flexural strength, surface roughness and crystalline structure of a leucite reinforced glass ceramic (IPS Empress CAD, Ivoclar Vivadent, Liechtenstein). A hundred fifty (150) discs were machined by CEREC inLab MC XL (Sirona, Alemanha) and distributed into five groups, n=30: C (control, no heat treatment), A-575 (annealed at 575°C during 15 min, followed by slow cooling and furnace opening at 200°C), A-790 (annealed at 790°C during 15 min, followed by slow cooling and furnace opening at 200°C), G (glazed at 790°C during 1,5 min, followed by fast cooling - immediate furnace opening) and GM (modified glaze, at 790°C during 1,5 min, followed by slow cooling and furnace opening at 200°C). Biaxial flexural strength was determined by the piston-on-three ball test (ISO 6872/2008). Weibull modulus (m) and characteristic strength (σ0) were calculated from the results. The surface roughness (Ra and Rz) was measured before and after the treatments. One specimen from each group was used for X-ray diffraction. A-790 produced the highest values of fracture strength (211.7 MPa). The values of σ0 obtained for the other tested regimens (A-575: 167.9 MPa, GM: 157.7 MPa and G: 153.7 MPa) were lower than those from the control group (187.7 MPa). The value of m was statistically similar between the groups. All heat treatments were able to reduce the mean roughness (Ra) of the specimens. The mean amplitude (Rz), showed a significant reduction only for the groups submitted to the annealing treatments (A-575 e A-790). The X-ray diffraction analysis revealed no changes in the crystalline phase (tetragonal leucite) of the material after the different heat treatments. Variations in the size of the leucite crystallites after thermal cycles were not significant. Thus, high values of fracture strength and decreased surface roughness for a leucite reinforced glass ceramic are achieved by annealing above the glass transition (Tg=625 ± 20ºC) after machining. This regimen (A-790) was capable to produce favorable structural reorganization of the material, without modifying its original crystalline structure. Annealing bellow the glass transition (A- 575) and thermal cycle for glazing (G and GM) significantly reduced the strength of the material.